DasArts. - Berends, Rob; Brouwer, Marianne; ten Cate, Ritsaert; Frisch, Norman; Gough, Richard; Hoogenboom, Marijke; Koel, Paul; Toebosch, Moniek; Van Kerkhoven, Marianne (Amsterdam : Stichting DasArts, 2000)
We cannot know what theater must or will be tomorrow. Participants in our post academic studies program have the responsibility to show us what the future will be ; and DasArts exists to support and inspire them in this process by helping them develop themselves and their craftsmanship. But, more importantly, DasArts is also here to assist them as they discover their own vision of the future, and the sense of purpose which supports that vision. DasArts is a multidisciplinary program which is designed and developed as we work. In this process we incorporate the individual student's personality along with the expertise offered by today's theater specialists, thus establishing a learning environment for all involved. A profound awareness of our surroundings, and of what is going on in the world around us, is a vital part of our focus on developing eager curiosity, which is required by all who wish to create. DasArts is a place where contemporaries pool ideas, opinions, reflections, problems, solutions. Any idea advanced by anyone involved with the DasArts program - specialist and student alike - will only become valid when the consequences of that idea are developed, tested and tried. DasArts is a unique laboratory for development, wherein the artist is the product... and the work the artist creates in this laboratory period is only a signal of the development of the artist him- or herself.
van den Akker, Ruud ; Bailey, Brett ; Balm, Nicole ; Beards, Michael ; van Bezouw, Zjef ; Brouwer, Marianne ; Chistie, Judie ; Cordua, Jördis ; D'Armagnac, Natasja ; David, Annelie ; Dobricic, Ingor ; Draisma, Janica ; Eberson, Hein ; Gough, Richard ; Geerlings, Paulien ; Gritter, Liesbeth ; Heggen, Gonnie ; Henegan, Cathy ; van der Heyde, Edwin ; Hoffmann, Jens ; Hommelshein, Christiane ; van der Horst, Robbert ; Hubert, Pierre-Alain ; Isadora, Alison ; de Jonge, Roberto ; Kaprow, Allan ; Katzenbauer, Ron ; Kawamata, Tadashi ; Krijnen, Cees ; Kruip, Germaine ; Lavern, Nadine ; van Lieshout, Joep ; van Loon, Wouter ; Mafaalani, Ola ; Mandersloot, Frank ; Musatov, Jasja ; Nevejan, Annick ; Odoardi, Stefano ; Otto-Sallies, Zulfah ; Pardo, Enrique ; Prins, Mechtild ; Racké, Quirine ; Raetz, Markus ; Rietstap, Ine te ; Roorda, Kees ; Ruud II ; Sauer, Ines ; van der Sijs, Mette ; Snijders, Corine ; Stuart, Meg ; Swain, Rachael ; Swarte, Rieks ; Toomato, Duro ; Torenbos, Betsy ; Wagenaar, Sjoerd ; Wilske, Judith ; Wits, Willem ; Wooldrik, Derk Jan ; Zacharias, Siegmar ; Zentschnig, Renate
Engels
boek